Two new Zn (II) bdc Metal-Organic Frameworks based on benzene 1, 4-dicarboxylic acid: Synthesis, Crystal structures, Luminescent properties and Electrochemical studies. (2020) - Omkaramurthy, BM.; Krishnamurthy, G.; Prasad, NL.
Abstract: Two new one-dimensional (1D) Zinc Metal organic frame works, [Zn (BDC) (DMF) RT] (or Zn-MOF-1) and [Zn (BDC) (DMF) MW] (or Zn-MOF-2), where H2 BDC = Benzene 1, 4 di-carboxylic acid, DMF = N, N-dimethylformamide, RT= Room temperature, MW= Microwave, have been synthesized through Room temperature and Microwave methods respectively. Zn-MOF-1; Zn-MOF-2 material was characterized by FTIR, Powder XRD, FE-SEM, Photo-luminescent, TGA and SXRD measurement. The electrochemical properties of these MOF electrodes were examined by using of Cyclic Voltammetry (CV), Galvanostatic Charge- Discharge (GCD) and Electrochemical Impedance Spectroscopic (EIS) techniques. Crystallographic studies show that the Zn-MOF-1 molecule has a one dimensional network in which the θ ranges from 6.86 to 54.92 with monoclinic P21 /c space group, with Volume = 1015.9(4) Å. In Zn-MOF-2 molecule θ ranges from 6.72 to 54.94 with monoclinic C2/c space group with Volume = 1265.9(3) Å respectively. In comparison with Zn-MOF-1 and Zn-MOF-2 based on BDC derivatives both MOFs show strong luminescence along with red-shift, which indicates that these are the potential candidates for various luminescent applications